High cure rates for HCV genotype 6 in advanced liver fibrosis with 12 weeks sofosbuvir and daclatasvir: The Vietnam SEARCH Study - Flower, B; McCabe, L; Ngoc, CL; Hung, LM; Phuong, LT; Trong, TD; Thi, TV; Kim, HVT; Tat, TN; Hong, DPT; Chau, ANT; Thi, TD; et al. (Oxford University Press, 2021)
Background Genotype 6 is the most genetically diverse lineage of hepatitis C virus (HCV), and predominates in Vietnam. It can be treated with sofosbuvir with daclatasvir (SOF/DCV), the lowest costing treatment combination globally. In regional guidelines, longer treatment durations of SOF/DCV (24 weeks) are recommended for cirrhotic individuals, compared with other pangenotypic regimens (12 weeks), based on sparse data. Early on-treatment virological response may offer means of reducing length and cost of therapy in patients with liver fibrosis.